A Comprehensive Bibliometric Study of Digital Leadership Influence on Technopreneurial Success - Gunawan, Ahmad; Hasyim, Wachid; Putih, Muhadar; Wirjawan, Tri Wahyu; Gopar, Ida Abdul; Stephanie, Stephanie (Pandawan, 2025)
This study investigates the role of digital leadership in fostering technopreneurship in Indonesia, a rapidly evolving sector shaped by technological advancements and digital transformation. As technological innovation and data-driven decision-making are central to the success of technopreneurs, understanding the role of leadership in this context is critical for sustainable growth. The primary aim of this research is to explore how digital leadership can enhance technopreneurship in Indonesia by promoting collaboration, innovation, and operational efficiency. The method a literature review and bibliometric analysis are employed to identify key trends and research patterns in digital leadership and its impact on the technopreneurship ecosystem. By analyzing data from various sources, the study provides an in-depth examination of the current state of the field. This research contributes a unique perspective by combining bibliometric analysis with traditional literature review, providing a comprehensive, data-driven approach to understanding how digital leadership drives technological innovation. It also emphasizes the challenges technopreneurs face, such as the digital skills gap and regulatory barriers, areas often overlooked in previous studies. While previous research has explored the general impact of digital leadership on business transformation, this study fills the gap by specifically focusing on Indonesia technopreneurship ecosystem and its unique challenges. The findings confirm that digital leadership plays a pivotal role in overcoming obstacles like unequal access to technology and driving innovation in technopreneurship. The study recommends strategies such as enhancing digital skills, investing in infrastructure, and fostering more flexible regulations to support the growth of technopreneurship in Indonesia.